The Impact of Administrative Empowerment on Job Performance in Publicly Traded Companies - mugahed, Faez; Naji, Fouad; Al-Rahoumi, Ahmed (Haka Vyza Media, 2025)
This study aimed to examine the impact of managerial empowerment on job performance in public joint-stock companies in Yemen. It used a quantitative approach and surveyed 433 employees from eight companies. The results reveal a high level of managerial empowerment practice in listed companies, with an average score of 5.51. Similarly, the average job performance score in the companies recorded an average of 5.55, indicating a high level of practice that enhances efficiency and competitiveness. There is also a strong positive impact of managerial empowerment on job performance, with the effect measured at (beta = 0.89). Based on these findings, the study recommends a comprehensive approach to employee empowerment, emphasizing a supportive and engaging work environment, effective task delegation, structured long- and short-term training, and a strong focus on employee motivation to improve job performance in public joint-stock companies.